Políticas públicas de promoção da saúde e da atividade física: programas e ações realizadas no município de Maringá-PR - Capdeboscq, Majorie Catherine (2014)
The 1970s were marked by the Health Reform and aimed to construct new values and awareness in Brazilian society regarding health foundation transformation of society. This reform culminated later in the creation of the Unified Health System through the Federal Constitution of 1988, in which the state takes as its main purpose the reduction of social inequalities, the promotion of the common good and to build a caring society without any forms of discrimination. The Unified Health System is a state policy used to improve the quality of life of Brazilians thus geared to the production of public health policies allow responding to health needs. Evidence has shown a positive association between healthy lifestyle habits with health and longevity, in this context, physical inactivity is a major public health problem which makes physical activity an effective tool for the promotion and general health care. With the spread of Potentially Healthy Municipalities Network the city of Maringa - PR deployed Maringa Healthy Program, which since 2006 takes action to promote health and prevention. This study aimed to analyze the politics of health promotion in the city of Maringa and the insertion of bodily / physical activity practices in these public policies. The study was conducted through documentary analysis on annual, existing reports on managerial and administrative records pertaining to the actions of health promotion at the Municipal Health Service in crowded Management in Health Promotion and Prevention Documents used for analysis were collected in the period 2006-2012, from the Program implementation. From the analysis of the data-note is some diversity in the actions of health promotion highlights the intersectoral work and meetings called Health Area. Note also that although many normative documents created by the Ministry of Health, scientific evidence benefits of physical activity and also the emphasis on public policies to promote physical activity in the National Health Promotion, few actions related to this area were carried out during the period.